(untitled) - Millon, Theodore (Hoboken, N.J., 2007)
Acknowledging the primacy of the whole person, Moderating Severe Personality Disorders: A Personalized Psychotherapy Approach takes into account all of the complexities of human nature - family influences, culture, neurobiological processes, unconscious memories, and so on--illustrating that no part of human nature should lie outside the scope of a clinician's regard.
Keywords: Personality disorders,Psychotherapy,Personality Disorders,Psychotherapy,Rối loạn nhân cách,Tâm lý trị liệu; Treatment,Therapy,Methods,Điều trị